In Service Together: University Students and Incarcerated Youth Collaborate for Change - Arthur, Deborah Smith (The prison journal, 2018)
Through the lens of two courses at Portland State University (PSU), this article addresses critical service learning pedagogy as transformational for both incarcerated youth and university students. In one course, PSU students share a writing/art workshop with youth in juvenile detention though The Beat Within (www.thebeatwithin.org). Another course brings together PSU students and young men incarcerated at MacLaren Youth Correctional Facility in an inside/out course format (www.insideoutcenter.org). Working collaboratively, students have developed a variety of service-learning projects. This article explores the impact of critical service learning courses on both incarcerated young people and university students.